Peripheral arterial disease (PAD) in diabetics: diagnosis and management- a narrative review - Zia Ur Rehman; Nanik Ram (Journal of the Pakistan Medical Association, 2023)
Peripheral arterial disease in diabetic patients is often overlooked due to associated neuropathy. The very first presentation of these patients is with an ischemic ulcer or toe gangrene. Diabetics have a very high amputation rate compared to non-diabetic patients due to diffuse multi-segmental disease in the calcified tibial arteries. Early detection of the condition is a challenge in these patients. Even ankle-brachial pressure index may not be reliable. Both surgical and endovascular options are effective in wound healing. Endovascular techniques include percutaneous transluminal angioplasty with and without stenting, sub-intimal angioplasty, percutaneous transluminal angioplasty with drug-coated balloons, covered stents, and use of atherectomy devices. The current narrative review was planned to discuss the essentials of diagnosing peripheral arterial disease in diabetic patients and its various treatment options. Key Words: Diabetic foot, Foot ulcer, PAD, Peripheral vascular disease.